Perirhinal cortex represents nonspatial, but not spatial, information in rats foraging in the presence of objects: Comparison with lateral entorhinal cortex - Deshmukh, Sachin S. (2012)
The medial temporal lobe (MTL) is involved in mnemonic processing. The perirhinal cortex (PRC) plays a role in object recognition memory, while the hippocampus is required for certain forms of spatial memory and episodic memory. The lateral entorhinal cortex (LEC) receives direct projections from PRC and is one of the two major cortical inputs to the hippocampus. The transformations that occur between PRC and LEC neural representations are not well understood. Here, we show that PRC and LEC had similarly high proportions of neurons with object-related activity (PRC 52/94; LEC 72/153), as expected from their locations in the “what” pathway into the hippocampus. However, LEC unit activity showed more spatial stability than PRC unit activity. A minority of LEC neurons showed stable spatial firing fields away from objects; these firing fields strongly resembled hippocampal place fields. None of the PRC neurons showed this place-like firing. None of the PRC or LEC neurons demonstrated the high firing rates associated with interneurons in hippocampus or medial entorhinal cortex, further dissociating this information processing stream from the path-integration based, movement-related processing of the medial entorhinal cortex and hippocampus. These results provide evidence for nonspatial information processing in the PRC-LEC pathway, as well as showing a functional dissociation between PRC and LEC, with more purely nonspatial representations in PRC and combined spatial-nonspatial representations in LEC.